Doing sociology : case studies in sociological practice - Price, Jammie; Straus, Roger A. (Roger Austin), 1948-; Breese, Jeffrey R., 1964- (Lexington Books, 2009)
This successor to the well-known Using Sociology covers standard topics found in any sociology textbook. Doing Sociology walks lay readers through the steps of doing real-life sociological practices as conducted by experts in the field. The contributors to this volume range from university and college faculty, government sociologists, and practitioners from the private sector. Each of the chapters is by intention and design a personal statement, a case study illustrating how the authorspractice sociology in their own words and style, giving readers a clearer understanding of what sociologists.